Metal‐Containing Block Copolymer Thin Films Yield Wire Grid Polarizers with High Aspect Ratio. (9th October 2013) - Kim, So Youn; Gwyther, Jessica; Manners, Ian; Chaikin, Paul M.; Register, Richard A.
<x xml:space="preserve">Abstract</x> Highly selective etch masks are formed by thin films of a polystyrene‐b‐poly(ferrocenylisopropylmethylsilane) diblock copolymer, PS‐PFiPMS, containing hemicylindrical domains of PFiPMS. These domains, with a period of 35 nm, are readily aligned through mechanical shear. Aligned PS‐PFiPMS templates are employed to fabricate high‐aspect‐ratio nanowire grids from amorphous silicon, which can polarize deep ultraviolet radiation, including 193 nm, at >90% efficiency. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>